Determination and analysis of the dispersive optical constants of the 2,9,16,23-tetraneopentoxyphthalocyaninatozinc(II) charge transfer complex with 2,3-dichloro-5,6-dicyano-p-benzoquinone thin film - Yakuphanoğlu, Fahrettin; Arslan, M; Yildiz, SZ (Elsevier, 2005)
Optical characterization of the charge transfer complex of 2,9,16,23-tetra neopentoxyphthalocyaninatozinc(II) with 2,3-dichloro-5,6-dicyano p-benzoquinone (DDQ) has been carried out using the transmittance T(lambda) and reflectance R(lambda) spectra. The optical band gap and Urbach energies were calculated from the optical absorption spectra. The optical absorption spectra show that the absorption mechanism is a direct transition. The optical constants (refractive index n, extinction coefficient k, dielectric constants epsilon(1), epsilon(2)) of the compound were determined. Optical dispersion parameters E-o and E-d developed by Wemple-DiDmenico were calculated. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: charge transfer compound; optical constants; optical band gap